(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Artificial Intelligence (AI) has become a transformative technology in modern digital infrastructures, enabling intelligent automation, enhanced security, and scalable computing environments. The development of an AI-enabled secure digital ecosystem plays a critical role in integrating cloud computing, enterprise automation, and cyber-physical systems (CPS). Such ecosystems allow organizations to process massive data streams, automate complex processes, and ensure secure communication between digital and physical components. Cloud computing platforms provide the scalable infrastructure required for deploying AI algorithms, while enterprise automation systems streamline organizational operations and improve efficiency. At the same time, cyber-physical systems integrate computational intelligence with physical devices such as sensors, industrial machines, and smart infrastructure to enable real-time monitoring and control. However, the rapid adoption of AI-driven digital ecosystems introduces significant challenges related to cybersecurity, data privacy, system interoperability, and governance. Secure digital architectures must incorporate advanced protection mechanisms including encryption, intelligent threat detection, and identity management frameworks to protect critical enterprise and industrial data. This research explores the architecture, technologies, and implementation strategies of AI-enabled secure digital ecosystems. The study also evaluates their role in enhancing cloud computing services, enabling enterprise automation, and supporting cyber-physical systems. Finally, the research highlights the advantages, limitations, and future directions of secure AI ecosystems in driving sustainable digital transformation across industries.